ANALISIS NILAI TAMBAH DAN ANALISIS EKONOMI ABON PISANG MUDA DENGAN PENAMBAHAN BUMBU MASAK HABANG - Mufrida Zein; Nuryati Nuryati; Mariatul Kiptiah; Ema Lestari (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Banana kepok is one fruit that has many nutritional value that can usually be good processed into various foods because banana kepok has a delicious textur and can made abon. Abon is a food that is done by drying process based on beef, chicken and fish, abon can also made from a variety of other basic ingredients by modifying the new the young banana shredded with a new taste of habang season. The aims of these reseach is to now the acceptance of consumers, the economic analyze, and the added value of the product. The organoleptic test results from banana formulations 150 gram, chicken meat 20 gram, habang cooking spices 30 gram, 500 ml coconut milk, and brown sugar 50 gram, much acceptable to consumers due to fine texture and good taste. As for the result of economic analysis obtained HPP of Rp 3.689/banana wrop abon banana with the addition of habang seosoning, the BEP 15 packs of ± 1 month marketing resolts get a turnover of Rp 1.200.000.00. The added value ratios abtained for the young banana fruit commodity amounted to 74% with the percentage of benefit is 88%.